(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Universal current monitoring system is new generation project based on the micro controller which is used to measure current. This gadget measures the current consuming by all the electric devices. This project is mainly helpful for uneducated and even educated people. This is mainly used to monitor the current consumed by the every electric gadget. At the same time the user can also monitor the current consuming values in the display which will be in the device and also in the mobile screen. In order to record all the data we can use the database or the user can manage with mobile. In order to check continuous electricity consumption, monitoring and displaying we are using the micro controller. The micro controller is central part to get the data from the all sensors and monitoring the data depending on the user condition. The user can operate this gadget by using smart mobile phone